IMPLEMENTASI MODEL PICTURE AND PICTURE PADA PEMBELAJARAN IPAS: ANALISIS PENINGKATAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Hadistia Siti Nuryani; Rayi Siti Fitriani; Silma Aghnia Supriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of the Picture and Picture learning model on the learning outcomes of fourth-grade elementary school students in Natural and Social Sciences (IPAS), particularly on the topic of energy transformation in everyday life. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 20 fourth-grade students selected through total sampling. Data were collected using pretest and posttest achievement tests and analyzed using the Shapiro–Wilk normality test, the Wilcoxon Signed Rank Test, and N-Gain analysis. The findings revealed a statistically significant difference between students' pretest and posttest scores (Z = –3.794, p < 0.001), with 18 out of 20 students (90%) demonstrating improved learning outcomes after the implementation of the Picture and Picture learning model. However, the average N-Gain score was 0.0276, indicating a low level of practical effectiveness. These findings suggest that although the Picture and Picture learning model significantly improves students' learning outcomes, the magnitude of improvement remains limited. The low N-Gain score may be attributed to the relatively high initial achievement of several students and the limited duration of the intervention, which was conducted in only one instructional session. Therefore, the implementation of the Picture and Picture learning model should be supported by longer instructional time, more varied visual learning materials, and sustained instructional strategies to maximize its impact on students' IPAS learning outcomes.